2004
DOI: 10.1007/s00467-004-1624-8
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease as a late complication of end-stage renal disease in children

Abstract: As in older adults, cardiovascular disease is the most important cause of death in adolescents and young adult patients with end-stage renal disease (ESRD) since childhood. This concerns patients on dialysis as well as transplant patients, despite the fact that a long duration of dialysis during childhood is an extra mortality risk factor. Left ventricular hypertrophy (LVH), aortic valve calcification, and increased arterial stiffness, but not increased arterial intima media thickening, are the most frequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
2
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 27 publications
0
52
2
2
Order By: Relevance
“…Adults with pre-emptive transplantations show a lower mortality rate, especially from cardiovascular conditions, and less morbidity from hypertension and left ventricular hypertrophy (8,17,28). As in adults, the primary cause of mortality in pediatric end-stage renal failure is cardiovascular, associated with hypertension (2,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Adults with pre-emptive transplantations show a lower mortality rate, especially from cardiovascular conditions, and less morbidity from hypertension and left ventricular hypertrophy (8,17,28). As in adults, the primary cause of mortality in pediatric end-stage renal failure is cardiovascular, associated with hypertension (2,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Data from the Late Effects of Renal Insufficiency in Children cohort study of 249 Dutch adult patients with onset of ESRD between 0 and 14 years of age demonstrated that the overall mortality risk of the patients with ESRD was 31 times that of age-matched Dutch citizens. 179 Cardiovascular disease accounted for 41% of all mortalities, with cardiac death becoming the most common cause of mortality after 10 years of receiving RRT. 179 Similarly, among 1380 patients with childhood-onset ESRD who died before aged 30 years, 23% of deaths were cardiovascular in origin; the cardiovascular death rate was 1000 times higher among children with ESRD than in the general population, and was 100 times higher among young adults with ESRD than in the general population.…”
Section: Hypertension In Pediatric Dialysis Patientsmentioning
confidence: 99%
“…179 Cardiovascular disease accounted for 41% of all mortalities, with cardiac death becoming the most common cause of mortality after 10 years of receiving RRT. 179 Similarly, among 1380 patients with childhood-onset ESRD who died before aged 30 years, 23% of deaths were cardiovascular in origin; the cardiovascular death rate was 1000 times higher among children with ESRD than in the general population, and was 100 times higher among young adults with ESRD than in the general population. 180 Although the number of patients with childhood-onset ESRD is small compared with the overall adult ESRD population, they constitute a unique group in whom control of cardiovascular risk factors is key to ensuring long-term survival.…”
Section: Hypertension In Pediatric Dialysis Patientsmentioning
confidence: 99%
“…Therefore, these factors are inadequate to characterize risk of cardiovascular damage in the pediatric population [41]. In our series, the most frequent risk factors were dyslipidemia, elevated HOMA, HT, and hyperparathyroidism, and the association with cardiovascular damage was adequate.…”
Section: Discussionmentioning
confidence: 68%